Spitz nevi in the classic histopathological pattern - lamb in wolf`s clothing - Gustavo Costa Verardino; Mayra Carrijo Rochael (Sociedade Brasileira de Dermatologia, 2015)
Spitz nevus is a benign melanocytic lesion and also one of the main differential diagnosis of melanoma. A descriptive and retrospective study of surgical specimens from patients with a diagnosis of Spitz nevus was conducted at two institutions in Niterói - RJ. 32 cases were analyzed. The most frequent histological subtype was compound (60 %), with a predominance of epithelioid cells (17 cases - 53%). Pagetoid spread was observed in 21 cases (68%). Maturation of melanocytes was present in 13 cases (81%). Kamino bodies were found in eight cases (25%). Atypical melanocytes were present in 18 cases (56%). Mitoses were present in 11 cases (34%). Detailed knowledge of the classical form of Spitz nevi is essential for the differential diagnosis with melanoma. However, no single criterium is definitive in the differential diagnosis between Spitz nevus and melanoma.